Resin Bonding to a Feldspar Ceramic After Different Ceramic Surface Conditioning Methods: Evaluation of Contact Angle, Surface pH, and Microtensile Bond Strength Durability - Amaral, Regina [UNESP]; Ozcan, Mutlu; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe [UNESP] (Quintessence Publishing Co Inc, 2011)
Purpose: To evaluate the surface pH, contact angle and microtensile bond strength (MTBS) of a resin-cement to feldspathic ceramic after various surface conditioning methods (SC).Materials and Methods: For pH measurements, 96 glass-ceramic disks were assigned into 12 groups (n = 8): SC-pH: No ceramic surface conditioning (control); SC2-pH: hydrofluoric-acid (HF) 9% 1 min; SC3-pH: SC2-pH+wash/dry; SC4-pH: SC3-pH+silane; SC5-pH: HF 4% 1 min; SC6-pH: SC5-pH+wash/dry; SC7-pH: SC6-pH+silane; SC8-pH: HF 5% 1 min; SC9-pH: SC8-pH+wash/dry; SC10-pH: SC9-pH+silane; SC11-pH: SC9-pH+neutralizer+wash/dry+sonic-cleaning; SC12-pH: SC11-pH+silane. For contact angle analysis, 40 disks were divided into 5 groups (n = 8): SC1-ca: no conditioning; SC2-ca: HF 9%+wash/dry; SC3-ca: HF 4%+wash/dry; SC4-Ca: HF 5%+wash/dry; SC5-ca: HF 5%+neutralizer+wash/dry+ultrasonic-cleaning. To evaluate the MTBS, 40 blocks were distributed into 4 groups SC (N = 10): SC1-bond: HF 9% 1 min+silane; SC2-bond: HF 4% 1 min+silane; SC3-bond: HF 5% 1 min+silane; SC4-bond: HF 5% 1 min+neutralizer+wash/dry+ultrasonic cleaning+silane. The resin cement was applied on the treated surfaces and bar specimens were produced that were submitted to 2 conditions: dry: immediate MTBS; TC: storage for 150 days and thermocycling 5000x. Fifty bar specimens were produced per group (n = 50). Contact angle and pHresults were submitted to one-way ANOVA and Tukey's test (alpha = 0.05). Microtensile data were submitted to two-way ANOVA and Tukey's test (alpha = 0.05). Results: pH values were significantly higher for SC6-ph (11.5 +/- 2.6) when compared to those of SC5-pH (2.7 +/- 0.4), SC8-pH (2.7 +/- 0.2) and SC2-pH (2.2 +/- 0.2) (p < 0.00, ANOVA). SC1-ca had the largest contact angle (48 16 degrees) and SC3-ca the smallest (9.4 +/- 7.7 degrees). The results of the MTBS test were as follows: independent of the storage condition, SC2-bond = SC1-bond > SC3-bond = SC4-bond. SC4-bond had the lowest MTBS value after TC (10.6 +/- 2.6 MPa).Conclusion: The acid neutralization step appears to be dispensable, since the washing/drying promoted similar pH values. That condition promoted a high contact angle and unstable resin microtensile bond strength to glass ceramic.
Keywords: glass ceramic; resin cement; pH; contact angle; bond durability